Dimensões políticas e jurídicas do dever do Estado com o direito à Educação: implicações da relação entre a esfera pública e privada por meio das OSCIPs - Silva, Deive Bernardes da (2011)
The objective of this research is to problematize the resignification that the 1995 State Reform causes in the State's obligation regarding the "right to education", by means of the partnerships between the private and public sectors, and especially with the Civil Societies' Organizations of Public Interest - CSOPI's. In this concept, the study proposes to analyze the political-judicial aspect proposed in the 1988 Federal Constitution, halting the impact of the separation of the State from public educational service which, in view of the Reform, became characterized as non-exclusive. The investigation was made through bibliographic research, in classic and contemporary works on this theme and documental research, especially in recent legislation which normatizes the CSOPI and of the "third division". In viewof the resultant analysis it was possible to verify that, in the political/jurisdictional/constitutional scope this is classified as innovative interpretations, having a colaborative application, as public social service, including education, is a State obligation as an educational right. Nevertheless, these services are tainted by the revolt of the CSOPI's, especially in the educational sphere. However, in the institutional field, the indispensibility of the educational programs offered to the communities is verified, as well as the non-removal of the State departments from their constitutional responsibility (societal) regarding educational rights.